Acinetobacter baumannii Isolated from Lebanese Patients: Phenotypes and Genotypes of Resistance, Clonality, and Determinants of Pathogenicity - Dahdouh, Elias; Hajjar, Micheline; Suarez, Monica; Daoud, Ziad (Frontiers in Cellular and Infection Microbiology, 2016)
Introduction:Acinetobacter baumannii is a nosocomial pathogen that usually affects critically ill patients. High mortality rates have been associated with MDR A. baumannii infections. Carbapenem resistance among these isolates is increasing worldwide and is associated with certain International Clones (ICs) and oxacillinases (OXAs). Moreover, this organism possesses a wide range of virulence factors, whose expression is not yet fully understood. In this study, clinical A. baumannii isolates are characterized in terms of antibiotic resistance, mechanisms of carbapenem resistance, clonality, and virulence. Materials and Methods:A. baumannii clinical isolates (n = 90) where obtained from a tertiary care center in Beirut, Lebanon. API 20NE strips in addition to the amplification of blaOXA−51−like were used for identification. Antibiotic susceptibility testing by disk diffusion was then performed in addition to PCRs for the detection of the most commonly disseminated carbapenemases. Clonality was determined by tri-locus PCR typing and doubling times were determined for isolates with varying susceptibility profiles. Biofilm formation, hemolysis, siderophore production, proteolytic activity, and surface motility was then determined for all the isolates. Statistical analysis was then performed for the determination of associations. Results and Discussion: 81 (90%) of the isolates were resistant to carbapenems. These high rates are similar to other multi-center studies in the country suggesting the need of intervention on a national level. 74 (91.3%) of the carbapenem resistant isolates harbored blaOXA−23−like including two that also harbored blaOXA−24−like. 88.9% of the A. baumannii isolates pertained to ICII and three other international clones were detected, showing the wide dissemination of clones into geographically distinct locations. Virulence profiles were highly diverse and no specific pattern was observed. Nevertheless, an association between motility, siderophore production, and biofilm formation was detected (p < 0.05). Conclusions: A very high rate of carbapenem resistance was detected, showing the need for immediate intervention. IC II and OXA-23-like were the most disseminated, reflecting their international dissemination. No specific associations were made between virulence and resistance, but instead associations among certain virulence factors were found. Investigating a more clonally diverse pool of isolates could help in the determination of associations between virulence and resistance.